Nitrogen in the environment : sources, problems, and management - Hatfield, Jerry L.; Follett, R. F. (Ronald F.), 1939- (Academic Press/Elsevier, 2008)
Nitrogen is one of the most critical elements for all life forms. In agricultural systems it is essential for the production of crops for feed, food, and fiber. The ever-increasing world population requires increasing use of nitrogen in agriculture to supply human needs for dietary protein. Worldwide demand for nitrogen will increase as a direct response to increasing population. Nitrogen in the Environment provides a wholistic perspective and comprehensive treatment of nitrogen. The scope of this book is diverse covering a range of topics and issues related to furthering our understanding of nitrogen in the environment at farm and national levels. Issues of nitrogen from its effects on crops and human nutrition to nitrogen in ground water, watersheds, streams, rivers, and coastal marine environments are discussed to provide a broad view of the problem and support scientists, researchers, and engineers in formulating comprehensive solutions. * The only source which presents an international, wholistic perspective of the effects of nitrogen in the environment with worldwide mitigation practices * Provides details on how to improve the quality of the environment by analyzing the development of emerging technologies * Develops strategies to be used by soil scientists, agronomists, hydrologists, and geophysicists for broad scale improvement of nitrogen efficiency.